Application of satellite navigation system for emergency warning and alerting. (July 2016) - Choy, Suelynn; Handmer, John; Whittaker, Joshua; Shinohara, Yuki; Hatori, Tomohiro; Kohtake, Naohiko
Abstract: One of the key responsibilities of any government is to communicate and disseminate safety information and warnings to the general public in case of an emergency. Traditionally, warnings are issued by the government through a broadcast approach using communication channels such as TV and radio. However this monopolistic approach is now challenged by new technologies and media capable of providing individualised warnings to personal mobile devices. Location-based emergency services and mobile alerts are becoming increasingly prevalent in the provision of emergency warnings. These new modes of emergency services have been adopted by several countries worldwide including Australia. One example is the Australian National Emergency Alert (EA) which is a telephone-based service enhanced with location-based capabilities. This paper introduces the concept of applying global satellite navigation systems such as the Japanese satellite system in the domain of emergency warning and alerting. The Japanese satellite warning system can be tailored to transmit real-time location-based emergency warnings to people's mobile devices while not being constrained by the limitations of ground-based communication technologies. A key advantage of satellite based communication is its high resilience to communication network overload and failure of ground systems and network infrastructure during a disaster. This enables people to obtain necessary information anywhere (outdoor) and anytime during times of disaster. A satellite-based warning system could also be integrated with existing warning services and be used as a complementary technology. This paper examines opportunities and challenges for using satellite navigation systems to deliver warnings and safety messages during emergencies and disasters. Highlights: Satellite navigation systems for emergency warning and alerting. The Japanese QZSS satellites can send wide area emergency messages The QZSS emergency alert system is independent of terrestrial communications infrastructure